Clinical skills required of ophthalmic nurse practitioners in tertiary level public hospitals in the Western Cape Province - U. Kyriacos; L. D. Scheepers; E. W. Hill; S. Jordan (AOSIS, 2009)
Background: South Africa has a 32-year history of training ophthalmic nurse practitioners (ONPs). The role and required skills and competencies of ONPs are not well documented in the international literature and are also absent from South African publications, including South African Nursing Council publications. Aim: This study aims to inform curriculum development and human resource planning by reporting on the clinical skills expected of ONPs by members of multidisciplinary ophthalmology teams. Method: A limited survey was undertaken in the ophthalmology wards and outpatient departments of three tertiary level hospitals in the Western Cape Province. A researcher-designed structured self-completion questionnaire was distributed to 30 ophthalmology practitioners: doctors, nurses and technicians. Respondents were asked to indicate the expected clinical skills of ONPs. Findings: All questionnaires were completed. All respondents favoured ONPs taking histories and performing emergency eye irrigations. There was less support for more complex procedures, such as B-scans. One-third of respondents did not expect ONPs to have skills in eight key areas, including examination of the anterior chamber angle for glaucoma. No statistically significant differences were found between responses of doctors and nurses, with one exception: more nurses (15/18) than doctors (4/10) had confidence in the ONP undertaking basic eye examinations for ocular motility (Fisher's exact test, P = 0 .035). Conclusion: In the study settings, ONPs are not using their specialist skills to the full. Not all practitioners were receptive to ONPs using the skills that they had acquired during their postgraduate diploma, threatening the educational effectiveness of this initiative.